Analysis Of Digital Services in Improving The Financial Performance Of Bank Of Kigali, 2021–2024 - Emmanuel Niyotwizeye (Journal of Indonesian Management, 2025)
This study investigates how digital services influence the financial performance of the Bank of Kigali between 2021 and 2024. A quantitative research design was applied using structural equation modeling with partial least squares (SEM-PLS) to examine the relationship between usability and accessibility, transaction functionality, security and trust, financial impact and loyalty, and customer satisfaction. Data were obtained from 366 active users of the bank’s mobile, internet, and agency banking platforms. The results show that transaction functionality is the strongest predictor of customer satisfaction (β = 0.547, p < 0.001), followed by security and trust (β = 0.225, p < 0.001), and financial impact and loyalty (β = 0.134, p = 0.046), while usability and accessibility was not significant (β = 0.026, p = 0.754). The model explained 59.8% of the variance in customer satisfaction. These findings demonstrate that effective and secure transactions, along with perceived financial benefits, play a central role in enhancing customer satisfaction, which subsequently drives financial outcomes. The study concludes that banks should prioritize investments in transaction efficiency and strong security systems while also addressing inclusivity to sustain competitiveness and long-term profitability.